The European Fund for Strategic Investments The Legacy : The European Fund for Strategic Investments as a game-changer for future economic stimulus programmes backed by EU public financing and for the European Investment Bank - European Investment Bank (European Investment Bank, 2021)
The inside story of the European Fund for Strategic Investments from 2015 to 2020 told through interviews with the Managing Director, Deputy Managing Director, members of the Investment Committee and final beneficiaries across Europe.The architects of this €500 billion-plus programme, the head of the EU bank and the president of the European Commission, describe the genesis of this financial pillar of the Investment Plan for Europe. Then the people who ran one of the biggest economic stimulus programmes in history detail how they did it-and what the lessons are for policymakers responding to new crises, including the economic shock caused by the COVID-19 pandemic.The European Fund for Strategic Investments has been one of the good news stories to emerge in a decade of economic uncertainty. It has gone well beyond its highly ambitious target of €500 billion in mobilised investments. The Juncker Plan has made a strong contribution to the 14 million jobs created in the EU between 2015 and 2020. It has become a success in co-financing projects that otherwise might not have been carried through. It has also charted the path towards new ways of financing. This is not only the case in relatively conventional areas, such as infrastructure, but also in sectors like research and innovation or the contribution to climate change mitigation. This is exactly what makes EFSI so ground-breaking: responding to the needs of the market through continuous financial innovation.The principle of the European Fund for Strategic Investments is here to stay. It has paved the way for its successor, the InvestEU programme, which is to be deployed under the 2021-2027 multiannual financial framework. This publication details why the programme was such a success.